Access for All! Neuro-architecture and Equal Enjoyment of Public Facilities - Gillen, Victoria (Disability Studies Quarterly, 2015)
Since the enactment of the Americans with Disabilities Act (ADA, 1990), many impaired Americans are no longer disabled by socially condoned conditions in the built environment. However, many people with cognitive and neurological impairments continue to face significant barriers to access, due to disabling environmental hyper-sensitivity and sensory processing disorders. These people are equally protected under the ADA, therefore mitigation is required. Neuroarchitecture, where consideration of the impact of the built environment on the central nervous system informs design paradigms, must complement current ADA compliance guidelines. This paper serves to open the topic to discussion, and is a call for attention, and action, for the removal of these generally unrecognized barriers to access and the equal use and enjoyment of public facilities.